EVALUATING THE EFFECTIVE NESS OF WATER UTIL TIES , TAKING INTO ACCOUNT THE SIGNIFICANCE OF ENVIRONMENTALLY FRIENDLY PRODUCTS - Аleksandr А. Tskhai (Водное хозяйство России: проблемы, технологии, управление)
An approach has been developed to analyze the efficiency of enterprises providing water supply and wastewater treatment services, taking into account the importance of environmentally friendly products. The study solved the problem of choosing the option for accounting for the transition of water utilities from quantitative to qualitative indicators, comparing the rate of change in efficiency for options for accounting for the factor of environmentally friendly products. The criteria for the stages of growth and development in the life cycle of a water utility – «efficiency for itself» and «efficiency for the environment» – are formulated. The classification of water utilities on the basis of growth (development) is formulated, the situation of reducing the level of efficiency of the water utility according to the introduced classification is characterized. The periods when the enterprises of the industry most effectively convert external resources into results for the population are identified. The transition to quality criteria changes the list of leaders among the reviewed enterprises in similar regional administrative centers of Russia in terms of population. This approach can be useful when evaluating water utilities for potential investments, as well as when creating a centralized system for setting tariffs based on reference values of water utilities‘ costs.